2(-4-3m)=-32

Simple and best practice solution for 2(-4-3m)=-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-4-3m)=-32 equation:


m in (-oo:+oo)

2*(-(3*m)-4) = -32 // + 32

2*(-(3*m)-4)+32 = 0

2*(-3*m-4)+32 = 0

2*(-3*m-4)+32 = 0

24-6*m = 0

24-6*m = 0

24-6*m = 0 // - 24

-6*m = -24 // : -6

m = -24/(-6)

m = 4

m = 4

See similar equations:

| 9(2)-6=3y | | 10x=20/12 | | .4x-0.003=5 | | 2(1+7a)=156 | | 4(2b+7)=92 | | 2(1+1a)=26 | | 3(4-4a)=36 | | 7(5w+8)=266 | | 3(7w+4)=96 | | -2(-2)=y | | -2(0)=y | | -2(2)=y | | 5(1+1d)=-20 | | 4(-5d-9)=64 | | -5=p+10 | | 6(2n-4)=0 | | 5(4-3t)=-40 | | .6x=.8+2.4 | | 6(-5t-1)=-336 | | 6(-6n-8)=96 | | 7(5t-4)=112 | | 5(-7t-6)=-170 | | 7(5k+4)=-7 | | 6x+9=2x | | 2x^3-5x^2+6x-15=0 | | 6(1+7k)=384 | | 6(-2)-3y=12 | | 2x+2(2x-3)=48 | | 7(-5+3d)=175 | | 7(-10+4b)=-322 | | 8(3x-11)=32 | | 2x-f=12 |

Equations solver categories